Driving energy: the enactment and ambitiousness of state renewable energy policy. (9th February 2015) - Berry, Michael J.; Laird, Frank N.; Stefes, Christoph H.
Abstract U.S. states have led the federal government in instituting policies aimed at promoting renewable energy. Nearly all research on renewable portfolio standards (RPSs) has treated RPS adoption as a binary choice. Given the substantial variation in the renewable energy goals established by RPSs, we propose a new measure of RPS ambition that accounts for the amount of additional renewable energy production needed to reach the RPS goal and the number of years allotted to reach the standard. By measuring RPS policy with more precision, our analysis demonstrates that many factors found to affect whether a state will adopt an RPS do not exert a similar effect on the policy's ambitiousness. Most notably, our analysis demonstrates that Democratic control of the state legislature is the most consequential factor in determining the ambitiousness of state RPS policies.